2018
DOI: 10.1111/pace.13473
|View full text |Cite
|
Sign up to set email alerts
|

Use of antimicrobial agent pocket irrigation for cardiovascular implantable electronic device infection prophylaxis: Results from an international survey

Abstract: This international survey suggests that, while there are little clinical data to support or discourage such practice, the usage of antimicrobial agent pocket irrigation for CIED infection prophylaxis is widely used in current practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…7 Trends among implanters regarding pre-operative antibiotic use are consistent with previously reported rates. 8 Specifically, the 97% of respondents utilizing appropriate antibiotics targeting Staphylococcal species fall in line with current guidelines set by the Class I level of evidence (LOE) A recommendation set by the American Heart Association. 9 However, our results also highlight the wide discrepancies seen with use of post-operative use of systemic antibiotics.…”
Section: Discussionmentioning
confidence: 86%
“…7 Trends among implanters regarding pre-operative antibiotic use are consistent with previously reported rates. 8 Specifically, the 97% of respondents utilizing appropriate antibiotics targeting Staphylococcal species fall in line with current guidelines set by the Class I level of evidence (LOE) A recommendation set by the American Heart Association. 9 However, our results also highlight the wide discrepancies seen with use of post-operative use of systemic antibiotics.…”
Section: Discussionmentioning
confidence: 86%
“…Even though the current guidelines did not recommend pocket irrigation with antibiotics to reduce pocket infection, one of the international surveys suggested that pocket irrigation with antibiotics during implantation is widely used in current practice (54% believe in the effectiveness of antibiotic pocket irrigation to reduce CIED infection; 33% are uncertain, and few consider this strategy ineffective 13% or offered no opinion) ( 20 ). A recent meta-analysis demonstrated a significantly protective effect on preventing PM infection with antimicrobial pocket irrigation, regardless of antimicrobial class ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly chosen antibiotics are Bacitracin (48%), vancomycin (39%), and cephalosporin (29%). [20] Kang et al [21] conducted a metaanalyses, including 10 studies, to investigate the protective effects of pocket irrigation regardless of antibiotics classes. The incidence of pocket infection decreased by about 59% with antibiotic irrigation compared with the use of saline.…”
Section: Discussionmentioning
confidence: 99%